Chemical and hydrophysical attributes of an Oxisol under coffee intercropped with brachiaria in the Cerrado - Rocha, Omar Cruz; Ramos, Maria Lucrécia Gerosa; Veiga, Adriano Delly; Guerra, Antonio Fernando; Bartholo, Gabriel Ferreira; Rodrigues, Gustavo Costa; da Silva, Juliano Escobar (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate the effect of irrigation and of the presence of brachiaria (Urochloa decumbens) between coffee (Coffea arabica) rows on coffee yield and on chemical and hydrophysical attributes of a Typic Haplustox. The study was conducted in the Cerrado region in Planaltina, Brasília, DF, Brazil, in a randomized complete block design, arranged in split-split plots, with four replicates. Water regimes (irrigated or rainfed) were assigned to the main plots, inter-row management systems to the subplots, and soil layers to the sub-subplots. The following soil attributes were determined: total organic carbon, total nitrogen, C/N ratio, carbon and nitrogen stocks, bulk density, aggregate stability, total porosity, macroporosity, low-retention microporosity, remaining microporosity, criptoporosity, and total and readily-available water, besides coffee yield. Irrigation of coffee plants, associated with brachiaria intercropped as a cover crop, increased coffee yield and favored chemical and hydrophysical soil attributes, improving soil structure and its ability to store water. Irrigation favors organic carbon stocks in the upper soil layers, whereas brachiaria favors soil physical attributes related to water availability to coffee.